1998
DOI: 10.1182/blood.v91.11.4084.411k05_4084_4091
|View full text |Cite
|
Sign up to set email alerts
|

The Notch Ligand, Jagged-1, Influences the Development of Primitive Hematopoietic Precursor Cells

Abstract: We examined the expression of two members of theNotch family, Notch-1 and Notch-2, and one Notch ligand, Jagged-1, in hematopoietic cells. Both Notch-1 and Notch-2 were detected in murine marrow precursors (Lin−Sca-1+c-kit+). The Notch ligand, Jagged-1, was not detected in whole marrow or in precursors. However, Jagged-1 was seen in cultured primary murine fetal liver stroma, cultured primary murine bone marrow stroma, and in stromal cell lines. These results indicate a potential role for Notch-Notch ligand in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
121
0
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(126 citation statements)
references
References 37 publications
4
121
0
1
Order By: Relevance
“…Despite various attempts aimed at depicting the factors that initiate spermatogenesis, the mechanisms involved in the determination of cell fate decisions during spermatogenesis remain obscure. Notch is a general regulator of cell fate determination during development in a wide range of tissues and organs throughout the animal kingdom (Varnum-Finney et al, 1998;Artavanis-Tsakonas et al, 1999). In this study, we demonstrated for the first time that Notch signaling protein components are present in the mouse testis, suggest-ing an important role for Notch in the regulation of spermatogenesis.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Despite various attempts aimed at depicting the factors that initiate spermatogenesis, the mechanisms involved in the determination of cell fate decisions during spermatogenesis remain obscure. Notch is a general regulator of cell fate determination during development in a wide range of tissues and organs throughout the animal kingdom (Varnum-Finney et al, 1998;Artavanis-Tsakonas et al, 1999). In this study, we demonstrated for the first time that Notch signaling protein components are present in the mouse testis, suggest-ing an important role for Notch in the regulation of spermatogenesis.…”
Section: Discussionmentioning
confidence: 58%
“…After ligand binding, the intracellular domain of Notch enters the nucleus and participates in the transcriptional control of downstream target genes (Weinmaster, 1997). It is generally believed that Jagged and Delta act as transmembrane proteins that interact with Notch receptors expressed on adjacent cells; however, there is also strong evidence to support the role of soluble forms of these ligands in Notch signaling (Varnum-Finney et al, 1998;Qi et al, 1999).…”
mentioning
confidence: 99%
“…Targeted disruption of each of these genes results in embryonic (Jagged1 and Delta4) or perinatal (Jagged2) lethality, suggesting that all have essential, non-redundant functions (Jiang et al, 1998;Xue et al, 1999;Duarte et al, 2004;Krebs et al, 2004). In vitro cultures with Jagged1 (Varnum-Finney et al, 1998;Karanu et al, 2000), Delta1 (Varnum-Finney et al, 2003) and Delta4 (Dando et al, 2005) have been used for expansion of haematopoietic progenitors or stem cells with the purpose of improving cell therapy protocols. However, to date there is no proof for the involvement of Notch ligands in the embryonic haematopoiesis and maintenance of adult haematopoietic progenitors as well as the individual contribution of these ligands in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Retrovirus-mediated expression of a constitutively active form of Notch-1 receptor in bone marrow cells can lead to increased hematopoietic stem cell (HSC) selfrenewal or to the immortalization of progenitor cells capable of undergoing lymphoid and myeloid differentiation (Varnum-Finney et al, 2000;Stier et al, 2002). Moreover, co-culture of HSCs with soluble or immobilized Notch ligands, or feeder cells expressing Jagged-1 or Delta-1, can maintain or even enhance HSC self-renewal in different assay systems (Varnum-Finney et al, 1998;Han et al, 2000;Karanu et al, 2000;Ohishi et al, 2002). Recently, we have shown that Jagged-1 immobilization on the stromal layer or Sepharose-4B beads is required for the induction of self-renewing divisions of days 28e35 cobblestone area-forming cells (CAFC).…”
Section: Introductionmentioning
confidence: 99%